2022
DOI: 10.1021/acsomega.2c07168
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Emission of Contorted Polycondensed Aromatic Hydrocarbons Made by Edge Extension Using a Palladium-Catalyzed Cyclopentannulation Reaction

Abstract: Contorted polycyclic aromatic hydrocarbons (PAHs), CPA1–2 and CPB1–2, bearing peripheral five-membered rings were synthesized employing a palladium-catalyzed cyclopentannulation reaction using specially designed diaryl acetylene synthons TPE and TPEN with commercially available dibromo- anthracene DBA and bianthracene DBBA derivatives. The resulting target compounds CPA1–2 and CPB1–2 were isolated in excellent yield and found to be highly soluble in common organic solvents, which allowed for their structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) have gained significant interest as prominent building blocks for various applications, among others, the design of conjugated macromolecules due to their large π surface and planarity. PAHs bearing interchangeable arrangements of five- and six- membered rings are described in the literature with various taxonomies, among others, cyclopenta-fused PAHs (CP-PAHs), , nonalternant conjugated polycyclic hydrocarbons (CPHs), or conjugated compounds bearing quinoidal groups . The high chemical, physical, and biological properties of CP-PAHs promote them as active component for myriad applications, ranging from optoelectronics, like, organic photovoltaic cells (OPVs), , organic field-effect transistors (OFETs), and light-emitting diodes (LEDs), to medical therapeutics, like their use in DNA intercalators for chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) have gained significant interest as prominent building blocks for various applications, among others, the design of conjugated macromolecules due to their large π surface and planarity. PAHs bearing interchangeable arrangements of five- and six- membered rings are described in the literature with various taxonomies, among others, cyclopenta-fused PAHs (CP-PAHs), , nonalternant conjugated polycyclic hydrocarbons (CPHs), or conjugated compounds bearing quinoidal groups . The high chemical, physical, and biological properties of CP-PAHs promote them as active component for myriad applications, ranging from optoelectronics, like, organic photovoltaic cells (OPVs), , organic field-effect transistors (OFETs), and light-emitting diodes (LEDs), to medical therapeutics, like their use in DNA intercalators for chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Conjugated copolymers made from [3 + 2] cyclopolymerization reactions have gotten noticeable interest as potential components for organic electronics 13,14 as they are characterized by unique structural features where the cyclopentannulated rings are incorporated into the backbone of the conjugated chains, 15,16 thus improving the polymers' structural rigidity and planarity, consequently enhancing the charge delocalization along the macromolecular chain. 17 Several studies have reported the synthesis of cyclopentannulated copolymers with remarkable optical and electrochemical properties for applications in optoelectronics. 14,18−20 It is noteworthy that our group has been the first to report the synthesis of specially designed cyclopentannulated copolymers as adsorbent materials revealing high uptake capacity of iodine and toxic organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the reaction was tested by making three prototypical monomers synthesized, as can be noticed from Scheme 1 which describes the synthetic pathway for derivatives BCM1−3. These building blocks were made by reacting 2 equiv of 9-bromoanthracene 1 with each of the contorted diethynyl aryl surrogates 2a−c using a typical cyclopentannulation reaction procedure17 which employs a catalytic amount of pd 2 (dba) 3 and P(o-tol) 3 in the presence of 5 equiv of KOAc and 2 equiv of LiCl in a deoxygenated 1:1 mixture of DMF/ toluene at 130 °C under argon for 1 day, thus providing 73− 95% of the target products in high purity, as confirmed by various analytical techniques such as NMR ( 1 H and 13 C), ESI-MS, and FTIR spectra (Figures S1−S3, S7−S9, S15−S20 in the Supporting Information file).…”
mentioning
confidence: 99%
“…PAHs are highly emissive with the long fluorescence lifetime and high quantum yield [35–37] . However, in the solid state, PAHs suffer greatly from π‐aggregation and excimer formation resulting in low photoluminescence (PL) and low quantum yield [7,38] . This drawback is known as the aggregation‐caused quenching (ACQ) [39,40] .…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] However, in the solid state, PAHs suffer greatly from π-aggregation and excimer formation resulting in low photoluminescence (PL) and low quantum yield. [7,38] This drawback is known as the aggregation-caused quenching (ACQ). [39,40] The ACQ property of luminogens makes them inefficient to be employed in the optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%